Восточная миссия: [повести] / Сергей Бортников - Бортников Сергей Иванович (Военные приключения)
Экземпляры: ф.14 (2012) / Инвентарный номер: 54567 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 83 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL